Feasibility study to establish the criteria for the design and creation of an academic journal in modern languages program (2017)
For students, investigators and academicians of any discipline, it is important to have means that spread their findings, making them public and provide a contribution to the scientific knowledge. One of these means is the academic journal, a basic instrument to communicate the progress of the investigations of any discipline. The inclusion of new Information and Communication Technologies (from now on ICT) has produced changes in the globalized world, not only in the scope of the academic information and communication, but also in the social structure of the dissemination of the scientific knowledge. This structure is integrated by authors, readers, journals and database editors, librarians, researchers and academicians; all of them, individuals that one way or another, have been participants of all these changes during this last decade.